Workers and Work in the Arts: Definitional Challenges and Approaches to Collective Action Among Arts and Creative Workers. Issue 3 (August 2023) - Skaggs, Rachel; Aparicio, Tania
In response to an era of transformation that deeply impacts workers and increased attention to worker collective action in the United States, this article documents some definitional and boundary challenges that constrain and facilitate unionization, collective action, and mutualism in arts and creative work. Arts workers are present across all strata of the labor market. Categories, such as art, commerce, craft, and entertainment, have often divided arts workers, blurring the boundaries around what work is and who counts as a worker. Despite these challenges, arts and culture workers present a compelling case for the promise and progress of collective action in an unwieldy occupational space.